Influence of the Technological Revolution on Human Resource Management - Tripathi, Prashant; Tripathi, Priyanka (Prabandhan: Indian Journal of Management, 2012)
The technological revolution is resulting in drastic shifts in structure in industry and society. These shifts have far-reaching implications for HR professionals. The technological revolution's impact in India is presented in this paper with implications for HR professionals.